PENINGKATAN KEMAMPUAN TAHSIN AL-QUR’AN PADA MAHASISWA PAI UIN AR-Raniry: - Sri Astuti A. Samad dan Heliati Fajriah (Al-Ishlah: Jurnal Pendidikan Islam, 2017)
This study discusses the effectiveness of peer tutoring method in improving the ability of tahsin al-Quran in Islamic Education students trough Bengkel Mengaji program at UIN Ar-Raniry. This research uses qualitative approach with data collection technique that is, interview and document study. While the data analysis techniques using content analysis, ie analyzing the contents of reading material or documents related to this research. The results of this study indicate that the method of peer tutoring has been proven effective in improving the ability of tahsin al-Quran in the Bengkel Mengaji program. Indicators that the program is effective can be seen in several ways, namely; 1) Organizing good materials; 2) Effective communication; 3) Mastery and enthusiasm to the subject matter; 4) Positive attitude towards students; 5) Giving fair value; 6) Dexterity in the learning approach; 7) Good student learning outcomes.